Neuropeptide Y receptor 1 and galanin receptor 2 (NPY1R-GALR2) interactions in the dentate gyrus and their relevance for neurogenesis and cognition - Beltran-Casanueva, Rasiel; Hernández-García, Aracelis; de Amo García, Paula; Blanco-Reina, Encarnación; Serrano-Castro, Pedro; García-Casares, Natalia; Fuxe, Kjell; Borroto-Escuela, Dasiel O.; Narváez, Manuel (Frontiers in Cellular Neuroscience, 2024)
This research demonstrates a sustained surge in neurogenesis within the dorsal dentate gyrus (DG) following intracerebroventricular injection of GALR2 and Y1R agonists.It is noted that co-delivering the M1145 GALR2 agonist and the Y1R agonist spurred neuroblast proliferation involving a protein in replication processes (PCNA+) and doublecortin (DCX+), a microtubule associated protein. However, quiescent neural progenitors and astrocytes remained unaffected.The study reveals a rise in putative Y1R-GALR2 heteroreceptor complexes.Significant enhancement in object-in-place memory consolidation was seen after a three-week treatment, hinting at a significant combined role of GalR2 and Y1R receptors in memory consolidation involving a putative formation of a Y1R-GalR2 heterocomplex, It may offer a promising avenue for future treatment strategies of learning and memory